MADRASAH MANAGEMENT TRANSFORMATION: SYSTEMATIC-BIBLIOMETRIC REVIEW OF INDONESIA’S RELIGIOUS MINISTRY POLICY 2019–2024 - Saugi, Wildan; Komariyah, Laili; Subagiyo, Lambang; Warman, Warman; Mansouri, Mabrouk Chibani (STAI Asy-Syukriyyah, 2025)
Previous studies on madrasah management in Indonesia remain largely descriptive and fragmented, with few attempts to integrate systematic reviews with bibliometric approaches. This study fills that gap by investigating the transformation of madrasah management under the Ministry of Religious Affairs’ 2019–2024 policy framework. Using a combined Systematic Literature Review (SLR) and bibliometric analysis with VOSviewer, we analyzed 149 academic articles published between 2015 and 2024, sourced from Scopus and Google Scholar. The findings reveal strong thematic concentrations on transformational leadership, strategic management, digital governance, and stakeholder participation, but also highlight persistent challenges such as regional disparities, weak policy implementation, and limited data-driven evaluation. Theoretically, this study contributes to the development of Islamic education management by contextualizing TQM, strategic management, and transformational leadership frameworks in the Indonesian madrasah context. Practically, it provides evidence-based recommendations for leadership training, equitable resource allocation, and inclusive digital transformation to support sustainable madrasah reform.